2023
DOI: 10.1039/d2ee04087e
|View full text |Cite
|
Sign up to set email alerts
|

Reduced 0.418 V VOC-deficit of 1.73 eV wide-bandgap perovskite solar cells assisted by dual chlorides for efficient all-perovskite tandems

Abstract: Wide-bandgap (wide-Eg) perovskites with bandgaps over 1.65 eV have great potential in constructing tandem solar cells (TSCs), however, they still suffer from large open-circuit voltage (VOC) deficits. Phase segregation and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 67 publications
0
25
0
Order By: Relevance
“…The higher built‐in electric field is conducive to driving the transport of photogenerated carriers and improving charge transfer and extraction, which is conducive to acquiring higher V OC . [ 9,51 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The higher built‐in electric field is conducive to driving the transport of photogenerated carriers and improving charge transfer and extraction, which is conducive to acquiring higher V OC . [ 9,51 ]…”
Section: Resultsmentioning
confidence: 99%
“…The higher built-in electric field is conducive to driving the transport of photogenerated carriers and improving charge transfer and extraction, which is conducive to acquiring higher V OC . [9,51] The inverted WBG PSCs were fabricated to evaluate the effect of TB treatment on device performance. Schematic of the perovskite solar cell device architecture we employ in Figure S22 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the wider range of bandgap tunability of HPs (%1.18-2.3 eV), they have been used for tandem device configuration (TDC), both in all perovskite configurations and in hybrid with Si or CIGS cells. [32,230,261,262] Detailed-balance calculations have shown that the limiting efficiency of a tandem device, considering an infinite number of subcells, can reach a demonstrated power conversion efficiency (PCE) of up to 69.9% under standard 1 sun illumination. [263,264] In a tandem device, PCE depends on how the subcells are connected.…”
Section: Tandem Configuration-hpscsmentioning
confidence: 99%
“…The details are demonstrated in the Experimental Section. Notably, considering the positive effect of chloride ions in improving the crystallization of perovskites, [46][47][48] chlorine ions were selected as anions for the ammonium salts. Figure S1 shows the molecular structures of PEACl and HACl 2 .…”
Section: Structure and Morphology Of Perovskitesmentioning
confidence: 99%